VARIABLE RADIO SOURCES AND TAKING INTO ACCOUNT OF IONOSPHERIC EFFECTS - Litvinenko, O. A.; Panishko, S. K. (Одеські астрономічні публікації, 2017)
Histograms and mean value of scintillations indexes are obtained for power cosmic radio sources on observations during 1998-2001. Using simulations it is showed that scintillations with periods more then 10 minutes give the error of measuring of amplitude of radio telescope response pattern within the limits from 5 into 50 per cent in dependence of strength of the scintillations.